1988
DOI: 10.1023/a:1015987223407
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The influence of lipid vehicles on the intestinal absorption of Ciclosporin was studied in vitro. The effect of the intestinal lipid digestion was considered on the partition of the drug from olive oil or middle-chain triglyceride (MCT) into phases of simulated intestinal content. The phases obtained after ultracentrifugation were analyzed for their Ciclosporin content and characterized for their lipid classes. For both lipid vehicles the presence of lipolysis products did not promote the partition of the drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Labrafil M 2125 CS is a complex mixture of materials including a mixture of mono, di and trigycerides of C18:2 (linoleic acid) and mono and di-esters of PEG300. Notably, the lipids in Labrafil M 2125 CS are long chain lipids and previous studies have shown that these are less readily digested in vitro than their medium chain comparators (32,40). Labrafil M 2125 CS also forms a relatively course dispersion on initial dilution into aqueous media.…”
Section: Solubilisation Of Cp-532623 After In Vitro Dispersion and Di...mentioning
confidence: 97%
“…Labrafil M 2125 CS is a complex mixture of materials including a mixture of mono, di and trigycerides of C18:2 (linoleic acid) and mono and di-esters of PEG300. Notably, the lipids in Labrafil M 2125 CS are long chain lipids and previous studies have shown that these are less readily digested in vitro than their medium chain comparators (32,40). Labrafil M 2125 CS also forms a relatively course dispersion on initial dilution into aqueous media.…”
Section: Solubilisation Of Cp-532623 After In Vitro Dispersion and Di...mentioning
confidence: 97%
“…Reports exist where in vitro lipid digestion models 154,155 have been used to assess the rate and extent of transfer of drugs from a prospective formulation, through the respective colloidal phases, to the final mixed micellar phase. 156 It has been proposed that the rate of transfer may be a crucial ratedetermining step in the absorption of highly lipophilic drugs, particularly from lipid-based formulations. 156 There are various animal models available for the confirmation of intestinal lymphatic transport 134,157 ; however, the best first step is estimation of the potential for transport from consideration of the partition coefficient and lipid solubility of the drugs.…”
Section: Table 3soral Bioavailability Parameters For Halofantrine Hclmentioning
confidence: 99%
“…156 It has been proposed that the rate of transfer may be a crucial ratedetermining step in the absorption of highly lipophilic drugs, particularly from lipid-based formulations. 156 There are various animal models available for the confirmation of intestinal lymphatic transport 134,157 ; however, the best first step is estimation of the potential for transport from consideration of the partition coefficient and lipid solubility of the drugs. If such calculations indicate that lymphatic transport may be a contributor to oral bioavailability, then further confirmatory experiments should be undertaken.…”
Section: Table 3soral Bioavailability Parameters For Halofantrine Hclmentioning
confidence: 99%
“…Further, some excipients are hydrolyzed in the gastrointestinal tract by lipases, thereby changing the solubilizing environment (17)(18)(19)(20). With the aim of distinguishing between the performances of lipidbased formulations in vivo and thereby facilitate the formulation development, several in vitro digestion models have been developed (1,(21)(22)(23)(24). Attempts have been made to correlate the solubilization of the drug in the aqueous phase generated during in vitro lipolysis with the in vivo performance of lipidbased formulations.…”
Section: Introductionmentioning
confidence: 99%